Determination of the influence factors on social commerce in SME: A review - Sutomo, Erwin; Nur Shamsiah, Abdul Rahman; Awanis, Romli (Penerbit Universiti Malaysia Pahang, 2020)
Social commerce refers to a new wave of e-commerce wherein traditional e-commerce companies use social media or social networking services to promote online transactions and shopping-related information exchanges. It has become a new critical hub of product sourcing for both businesses and individuals. Still, there is a scarcity of identifying what significantly contributes to success. This study aim to investigate the determinants factor that influence the implementation of social commerce. The results of this study are TAM is a method that is widely used for social commerce implementation, while the factors that influence the implementation of social commerce are trust, perceived usefulness, information quality, ease of use, enjoyment, and service quality.